METACOGNITIVE READING STRATEGY AWARENESS IN READING COMPREHENSION OF NARRATIVE TEXT : A Case Study - Kurniawan, Muhammad Yusuf (2015)
This study aims to find out the participants' responses toward the implementation of metacognitive strategy to helpparticipants' reading comprehension of narrative text. This study employed a qualitative case study approach. The participants of this study were 6college students of UPI. The data were obtainedfrom the interview, observation, and test.The results of this study from interview showed that participants could read the text more strategically by dividing reading process into three: Planning (17%), Monitoring (33%), and Evaluation (50%). It indicated that participants were able to use metacognitve strategy to read and complete the reading comprehension test. On the other hand participants used top-down model as a model to read the reading comprehension text fluently. The findings from the test and observation indicated all the participants could answer the reading comprehension test correctly. Keywords: Reading Comprehension, Metacognitive Strategy, Narrative Text Penelitian ini bertujuan untuk mengetahui tanggapan peserta-peserta terhadap pelaksanaan strategi metakognitif untuk membantu peserta-peserta membaca pemahaman teks naratif. Penelitian ini menggunakan pendekatan kualitatif studi kasus. Peserta penelitian ini adalah 6 mahasiswa UPI. Data diperoleh dari wawancara, observasi, dan tes. Hasil penelitian dari wawancara menunjukkan bahwa peserta bisa membaca teks lebih strategis dengan membagi proses membaca menjadi tiga: Perencanaan (17%), Pemantauan (33%), dan Evaluasi (50%). Hal ini menunjukkan bahwa peserta mampu menggunakan strategi metakognitf untuk membaca dan menyelesaikan tes pemahaman membaca. Di sisi lain peserta-peserta menggunakan model top-down sebagai model untuk membaca teks pemahaman bacaan dengan lancar. Temuan dari tes dan observasi menunjukkan semua peserta bisa menjawab tes pemahaman membaca dengan benar. Kata kunci: Pemahaman membaca, Metakognitif Strategi, Teks Narasi